Organocatalytic promoted coupling of carbon dioxide with epoxides: a rational investigation of the cocatalytic activity of various hydrogen bond donors. Issue 9 (17th September 2015) - Alves, M.; Grignard, B.; Gennen, S.; Mereau, R.; Detrembleur, C.; Jerome, C.; Tassaing, T.
<x xml:space="preserve">Abstract</x> A rational investigation of the cocatalytic activity of a series of commercially available hydrogen bond donors (HBDs) for the synthesis of cyclic carbonates from CO2 and epoxides under mild conditions.